A national study to assess pharmacists’ preparedness against COVID-19 during its rapid rise period in Pakistan - Hussain, Iltaf (PLoS One, 2020)
To evaluate the pharmacist’s preparedness against the COVID-19 during its rapid rise period in Pakistan, an online cross-sectional study was carried out from March 30 to May 22, 2020 among the pharmacists using a pre-validated self-administered questionnaire. A total of 1149 participants completed the survey, amongst which 430(37.9%) were working as retail pharmacists, 216 (18.8%) as community pharmacists, and 213(18.5%) as hospital pharmacists. The mean COVID-19 knowledge score of the participants was 6.77±0.5, which indicated that 84% of them had good knowledge about COVID-19. The multiple linear regression model revealed that attitude was significantly associated with gender (p = 0.001), marital status (p<0.0001) and resident (p = 0.013). The mean practice score was 2.85±0.4, showing that 94% of the participants were following adequate preventive practices against this infection. The results from this study suggest that Pharmacists demonstrated good knowledge, positive attitudes, and acceptable practices regarding COVID-19.